Laser measured rate equations with various transmission coders for optimum of data transmission error rates - Hazem M. El-Hageen; Aadel M. Alatwi; Ahmed Nabih Zaki Rashed (Institute of Advanced Engineering and Science, 2020)
The present study has outlined laser-measured rate equations with various transmission coders for optimum data transmission error rates. Various modulation transmission coders are employed, such as a pulse position modulation coder, a differential pulse intensity modulation coder, and a four band/five band modulation transmission coder, in order to create optimized data rates of up to 40 GB/s for a fiber extension length of up to 100 km. This study has emphasized the important role of pulse position modulation transmission coders, which exhibit superior performance in max. Q parameter and min. data error rates, even for high data rate transmission.